Efficient fertigation for improvement of yield and quality of chilli production in soilless culture under protected cultivation - Salamat, Siti Suliza (2013)
Chilli (Capsicum annum L.) is an important vegetable crop in Malaysia and cultivated commercially in fertigation system. In 2011, Malaysia produced 32 780 metric tons of chillies with growing area at 2,559 ha. Nutrient and media are essential inputs that required for plant development. In fertigation system, fertilizer is supplied in nutrient solution form and been efficiently utilized. Thus, main objective of this study is to determine fertigation approaches that lead to efficiency for fertigation management. The studies were carried out on chilli plants grown under simple rain shelter structures in lowland of Malaysia. In the studied, plants were grown in three different media combinations (100% coconut coir dust (CD) as based media; 80 % CD + 20 % empty fruit bunch (EFB) compost and 70 % CD + 30% EFB as additive to the basic CD media with four different formulation. All those formulations used two different quantities of 400ml and 700ml fertilizer concentration. This study found that Copper Formulation and 400ml concentration resulted in a higher growth and yield of chilli plants (justify results). From this study, the suitable conductivity for chilli cultivation was investigated in the following trial. The study involved the use of different electrical conductivity (EC) of Copper Formulation. In this study, plants were subjected to 1.5 and 2.0 dS/m. The experiment was conducted in a CRD with three replications. The results indicated that Cooper Formulation with EC 2.0 dS/m. In conclusion, efficient fertigation can be achieved by cultivation chilli plants in CD mixtures with 30% EFB compost with 2.0 dS/m EC of Copper Formulations. Higher growth and yield performances were attributed by utilizing additive soilless substrate resulted in better growth and yield of plant. Proper managements of electron conductivity and nutrient application are vital to achieve cost effective production.